The electrochemical and spectroelectrochemical properties of metal free and metallophthalocyanines containing triazole/piperazine units - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The synthesis and characterization of novel peripherally tetra [1,2,4]-triazole substituted metal-free phthalocyanine and its metal complexes (Zn(II), Ni(II), Pb(II), Cu(II) and Fe(II)) and the investigation of electrochemical and spectroelectrochemical properties of metal-free, Zn(II), Pb(II), Fe(II) phthalocyanines were performed for the first time in this study. Electrochemical characterizations of the complexes were performed with voltammetric and in situ spectroelectrochemical measurements. Voltammetric responses of the complexes supported the proposed structures, since complexes bearing redox inactive Pc ring metal centers just gave Pc based electron transfer reactions, while iron phthalocyanine went to metal based electron transfer reaction in addition to the Pc based ones. Electron withdrawing nature of [1,2,4]-triazole substituents shifted the redox processes toward the positive potentials. All complexes were electropolymerized during the oxidation reactions in dichloromethane (DCM) solvent. Types of the metal center of the complexes altered the electropolymerization reactions of the complexes. Spectra and colors of the electrogenerated redox species of the complexes were also determined with in situ spectroelectrochemical and in situ electrocolorimetric measurements. (C) 2015 Published by Elsevier B.V.
Keywords: Synthesis; Phthalocyanine; Triazole; Electrochemistry; Spectroelectrochemistry; Soluble; IN-SITU SPECTROELECTROCHEMISTRY; SUBSTITUTED PHTHALOCYANINES; PHOTOCHEMICAL PROPERTIES; COBALT PHTHALOCYANINE; LEAD PHTHALOCYANINES; MODIFIED ELECTRODE; CATALYTIC-ACTIVITY; DERIVATIVES; COMPLEXES; BEHAVIOR